2020
DOI: 10.1186/s13046-020-01697-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Hsa_circ_0001944 promotes the growth and metastasis in bladder cancer cells by acting as a competitive endogenous RNA for miR-548

Abstract: Background Bladder cancer (BC) is a common genitourinary malignancy worldwide. Circular RNAs (circRNAs) participate in cancer development, including BC; thus, the roles of circRNAs in this process have attracted significant attention. Methods In this study, high-throughput sequencing was used to analyze circRNA expression profiles in BC tissues. We performed RT-qPCR to determine hsa_circ_0001944 expression in BC tissues. We used fluorescence in situ hybridization (FISH) to detect hsa_circ_0001944 expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“… 14 In addition, high circ_0001944 expression facilitated bladder cancer advancement by upregulating PROK2 via sponging miR-548. 13 Therefore, we concluded that circ_0001944 played a promoting effect on cell tumor growth and glycolysis in NSCLC.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“… 14 In addition, high circ_0001944 expression facilitated bladder cancer advancement by upregulating PROK2 via sponging miR-548. 13 Therefore, we concluded that circ_0001944 played a promoting effect on cell tumor growth and glycolysis in NSCLC.…”
Section: Discussionmentioning
confidence: 88%
“…Circ_0001944 had been uncovered to exert a promoting influence on the tumorigenesis of bladder cancer. 13 Moreover, circ_0001944 was highly expressed in NSCLC tissues. 14 At present, the role of circ_0001944 in NSCLC has not been verified.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Hsa_circ_0001944 is another tumor-promoting circRNA in bladder cancer that functions as an endogenous miRNA competitor to regulate PROK2 expression by binding to miR-548. 8 Chen et al suggested that oncogenic circAGO2 drives cancer progression by facilitating HuR-repressed functions of AGO2-miRNA complexes. Hsa_circ_000984 affects colorectal cancer cell invasion, migration and growth by competing with cell cycle-associated proteins for sponging of miR-106b.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, circRNAs have been reported to play a critical role in the pathogenesis of several cancers, such as ovarian cancer, hepatoblastoma and bladder cancer. 8–10 The aim of this study was to investigate and validate potential therapeutic targets of circRNAs in NB.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Hsa_circ_0001944 was considered to be a potential biomarker for bladder cancer, which served as a miR-548 sponge to facilitate cell migration and invasion via PROK2. 13 In addition, circ_0000376 was found to facilitate NSCLC cell glycolysis, viability and metastasis through regulating the miR-1182/NOVA2 network. 14 …”
Section: Introductionmentioning
confidence: 99%